Utilizing TRIPS flexibilities for public health protection through south-south regional frameworks - Musungu, Sisule F. (South Centre, 2004)
"This study provides the conceptual as well as a strategic basis for further thinking and decision-making on how effectively to use TRIPS [Trade-Related Aspects of Intellectual Property Rights] flexibilities for public health purposes through regional South-South mechanisms and cooperation. The study should, however, not be seen as the A to Z of regional approaches to the use of TRIPS flexibilities, but rather as a first step. Critical issues with a regional dimension that need to be further explored through empirical research and discussions are identified and explored."--Executive summary.